Axilla Reconstruction Post Burn Contracture: Thoracodorsal Artery Flap Versus Local Flap and Skin Grafts - Rashid, Sobia; Akhlaq Ali Khan, Faisal; Gulzar, Sadaf; Sami, Waqas; Ali, Hyder; Kiran, Saba (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Burns are a prevalent worldwide morbidity that frequently results in contractures that impede function and appearance, especially in the axilla, which has a major impact on upper limb mobility. Aim: To compare the functional results of local flaps with skin transplants versus Thoracodorsal artery flaps for axilla repair following burn contracture. Methods: A prospective comparative study was conducted. In the Department of Plastic and Reconstructive Surgery, thirty patients were split into two groups for a prospective comparative study. Group B underwent local flaps utilizing skin grafts, whereas Group A underwent thoracodorsal artery flaps. An analysis was conducted on pre- and post-operative shoulder joint abduction, complications, and demographic factors. Result: The two groups' post-operative shoulder abduction did not significantly differ, according to the results; however, younger patients and those with concomitant conditions including diabetes and hypertension were more likely to benefit from thoracodorsal artery flaps because of increased vascularization. The study discovered that middle-aged individuals typically had local flaps, but younger patients frequently had thoracodorsal artery flaps. Though not statistically significant, the gender distribution revealed a trend with more males obtaining local flaps and more females receiving thoracodorsal artery flaps. Thoracic dorsal artery flaps were substantially more common in patients with diabetes and hypertension. Practical Implication: The higher prevalence of thoracodorsal artery flaps in patients with diabetes and hypertension underscores importance of choosing flaps that provide better vascular support for patients with compromised vascular health. Conclusion: The findings highlight the significance of considering patient-specific criteria when choosing a flap, as thoracodorsal artery flaps provide better vascular support and are advantageous for patients with compromised vascular health. These results emphasize the need for customized surgical planning to improve results in post-burn contracture axilla repair. To enhance patient care and further improve surgical protocols, future research should concentrate on long-term results.